DBW222 (Karan Narendra): A new high-yielding, lodging-tolerant wheat variety for North Western plains of India - Mishra,Chandra Nath (2020)
Abstract DBW222 is characterized by potential yield of 8210 kg ha-1 under high fertility when sown in timely conditions in North India. It possesses better agronomic attributes and has better adaption to sowing time, high rust resistance, quality attributes, and lodging tolerance because of a shorter 2nd internode and wider diameter.